Total synthesis of (+)-petromyroxol - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The total synthesis of (+)-petromyroxol establishing its absolute configuration has been accomplished. The strategy developed employs easily accessible carbohydrate building blocks and comprises flexible and scalable chemistry that allowed the synthesis of (+)-petromyroxol along with its three diastereomers varying the stereochemistry mainly at C5 and/or C6. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Glucose diacetonide; Petromyroxol; Pheromone; Sea Lamprey; Total synthesis

Total synthesis and structural assignment of hexaketide xylarinolb and its C1-epimer - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Asian Journal of Organic Chemistry, 2016)
The total synthesis of two isomeric hexaketides isolated along with sordarial, which have the proposed relative arabino and ribo configurations, has been executed. A Rh-catalyzed [2+2+2]-alkyne cyclotrimerization has been employed as the key reaction to construct the central dihydroisobenzofuran core. The absolute configuration of the xylarinolB hexaketide has been established as l-arabino. This is the first natural product of this family for which the absolute configuration has been determined, and this can be extended to provide structural details of several of related hexaketides.
Keywords: hexaketides; sordarial; Wilkinson's catalyst; xylarinolB; {[2+2+2]-cyclotrimerization